2011
DOI: 10.2319/041211-265.1
|View full text |Cite
|
Sign up to set email alerts
|

Do enamel microabrasion and casein phosphopeptide-amorphous calcium phosphate affect shear bond strength of orthodontic brackets bonded to a demineralized enamel surface?

Abstract: Objective: To evaluate and compare the effects of enamel microabrasion, casein phosphopeptideamorphous calcium phosphate (CPP-ACP), and their combination on the shear bond strength (SBS) of orthodontic brackets bonded to demineralized enamel surface. Materials and Methods: One hundred human first premolar teeth were randomly allocated to one of five groups. Group I was considered as the control of other groups. For the remaining groups, demineralization was performed via solutions. In group II, brackets were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 22 publications
(32 reference statements)
1
28
2
Order By: Relevance
“…This result is in accordance with the study by Baysal and Uysal. 13 On the other hand, in contrast to our study, Sanders et al 21 indicated similar SBS values of orthodontic brackets bonded to microabraded and nonmicroabraded tooth surfaces. The different results may be due to the differences in enamel conditions and abrasives used.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…This result is in accordance with the study by Baysal and Uysal. 13 On the other hand, in contrast to our study, Sanders et al 21 indicated similar SBS values of orthodontic brackets bonded to microabraded and nonmicroabraded tooth surfaces. The different results may be due to the differences in enamel conditions and abrasives used.…”
Section: Discussioncontrasting
confidence: 55%
“…In the studies mentioned above, natural enamel surfaces were used. On the other hand, Uysal et al 12 compared the effects of fluoride and CPP-ACP and Baysal and Uysal 13 compared the effects of microabrasion and CPP-ACP on the SBS of orthodontic brackets bonded to demineralized enamel and found no significant differences between the control and CPP-ACP groups. In both studies, pretreatment of artificially demineralized surfaces with remineralization procedures appeared to restore decreased SBS values of orthodontic brackets, which is in accordance with the findings of our study.…”
Section: Discussionmentioning
confidence: 99%
“…CPP-ACP has been studied mainly with metal brackets to increase SBS. SBS was evaluated with human [Xiaojun et al, 2009;Baysal and Uysal, 2011;Tabrizi and Cakirer, 2011;Uysal et al, 2011] and bovine teeth [Kecik et al, 2008]. An increase in bond strength was found for bovine teeth when applying CPP-ACP paste, fluoride plus CPP-ACP or acidulated phosphate fluoride as compared to the control teeth where no pretreatment was applied [Kecik et al, 2008].…”
Section: Modification Of Shear Bond Stress (Sbs)mentioning
confidence: 99%
“…Clinicians can help patients to overcome white spot lesions using some pretreatment procedures on the enamel. 16 Besides, mineral content on enamel may also affect the attachment of orthodontic brackets. On demineralized enamel, for instance because of the presence of caries lesions or post bleaching, the bonding strength of the orthodontic bracket tends to be lower compared to the bracket bonding on normal enamel.…”
Section: Discussionmentioning
confidence: 99%